Recent Jurisprudence on Political Law (2022)
This article provides an overview of select Supreme Court decisions on political law promulgated last 2021. They tackle various concepts under political law, namely the Bill of Rights, social justice, and presidential powers and privileges. Part I discusses how the Supreme Court fixed the bounds of constitutionally guaranteed freedoms, most notably on free speech and expression. Part II focuses on the State's policy of promoting equal rights and opportunities to all Filipinos, such as those pertaining to academic freedom and cultural heritage and ancestral domains. Part III illustrates the broad applicability of presidential immunity and the scope of the president's powers as the chief architect of the country's foreign policy.
Keywords: Jurisprudence; Legal judgments; Philippine Politics